Host feeding preference of culex quinquefasciatus (Diptera:Culicidae) in Monterrey Northeastern, Mexico - Elizondo Quiroga, Armando Erick; Flores Suárez, Adriana Elizabeth; Elizondo Quiroga, Darwin; Ponce García, Gustavo; Blitvich, Bradley J.; Contreras Cordero, Juan Francisco; González Rojas, José Ignacio; Fernández Salas, Ildefonso; Beaty, Barry J.; Mercado Hernández, Roberto (2006)
Studies were conducted to determine the host selection patterns of Culex quinquefasciatus in the municipalities of Guadalupe and Escobedo near Monterrey, northeastern Mexico. Mosquitoes were captured inside and outside houses. Chickens and humans were the most common blood sources for all Cx. quinquefasciatus females, accounting for nearby 70% of blood meals. Human blood was detected by enzyme-linked immunosorbent assay in 36.4% and 28.4% of engorged females resting inside houses in Guadalupe and Escobedo, respectively. The proportions of indoor resting females fed on chicken blood were 38.7% and 56.7%, respectively. The weighted and unweighted human blood index (HBI) values were calculated, by using indoor and outdoor data, from the proportions of humanfed mosquitoes. Weighted means (HBI) estimates for Guadalupe and Escobedo were 23.0% and 15.4%, respectively. The forage ratios (FRs) for humans were <1.0 (with or without chicken populations); consequently, it seems that these mosquitoes feed on humans with less frequency in comparison with chickens, horses, and pigs. The FRs for chickens were the highest of all available hosts (1.7 and 3.2), and they were the most abundant hosts in Escobedo, and the second most abundant in Guadalupe, indicating a selective bias of Cx. quinquefasciatus for chickens (i.e. ornithophagic).